Unveiling Underlying Factors Affecting Consumer Loyalty of Sweetmeat Products: Findings from SEM and fsQCA - Rana, Md. Sohel; Uddin, Md. Shawan Uddin; ., Md. Nuruzzaman; Bhadra, Samir; Uddin, Md. Kutub; Rana, Md. Sohel (Journal of Posthumanism, 2025)
This study aims to quantify the determinants that impact consumer satisfaction and consumer loyalty within the sweetmeat food industry. The current study finds that food quality, food safety, pricing, and trust have a substantial impact on consumer satisfaction and loyalty which is supported by the theory of planned behavior, S-O-R, and equity. A convenient sampling method was employed to collect survey data from 279 participants who are engaged in the sweetmeat industry in the northern region of Bangladesh. Subsequently, the raw data was analyzed by adopting symmetric (PLS-SEM) and asymmetric (fsQCA). The study reveals that while food safety doesn't significantly impact consumer satisfaction, high food quality, price, and trust boost satisfaction. Pricing and trust don't significantly impact loyalty. fsQCA supports PLS-SEM results, highlighting nine causal configurations for high consumer loyalty.